Evaluation of Temporary Evacuation Shelter (Tes) For Tsunami In Banggae Timur, Majene Based on Location-Allocation Analysis - Erwin, Muh. Alfarezi; Priadmodjo, Anggit; Munaja, Rahmiyatal; Mulawarman, Ade; Mukhlis, Jafar; Wahyudi, Adip (Journal of Green Science and Technology, 2025)
Majene Regency, specifically the Banggae Timur District, is at considerable risk of tsunamis due to its coastal location and increasing urban density. This research evaluates the effectiveness of current Temporary Evacuation Shelters (TES) using a spatial analysis methodology combined with location-allocation modeling. The methodology included tsunami inundation mapping utilizing historical data, identification of building points, analysis of TES capacity, and modeling of service areas within a maximum evacuation radius of 935 meters.The study concentrated on two specific TES: Prasamya Stadium and the Majene Regency Police Station. Although both locations possess adequate capacity for hosting evacuees, they are situated within high-risk tsunami inundation zones (5–6 meters), making them inappropriate for safe evacuation. Spatial allocation modeling indicates that these TES predominantly serve the western section of Banggae Timur District, resulting in considerable underservicing of eastern coastal areas and increased risk. Of the 2,774 houses located within the tsunami inundation zone, 1,506 are currently unserved by the existing TES. The findings highlight the necessity of identifying and establishing new TES in safer, elevated areas with enhanced accessibility to improve evacuation coverage and safety. This study emphasizes the importance of spatial modeling in enhancing evidence-based disaster mitigation planning. It offers precise, data-driven insights for optimizing emergency infrastructure and minimizing population risk exposure in urban areas susceptible to tsunamis.